Real-time phase measurement of optical vortex via digital holography - Qiu, Huaibin; Liu, Xiaosong; Wang, Kaiqing; Dou, Jiazhen; Di, Jianglei; Qin, Yuwen (Frontiers in Physics, 2023)
Real-time phase measurement is of great importance in promoting the study of optical vortex. However, it cannot be recorded in real-time due to the limitation of the exposure time of recording device in the experiment. Therefore, based on temporal and spatial evolution correlation of optical phase, a real-time phase measurement method of optical vortex generated by an acoustically-induced fiber grating is proposed based on digital holographic reconstruction algorithm. First, a series of holograms are continuously recorded using a low frame rate CCD. Then, the evolution of optical vortex over time is translated into changes in transmission distance. And the unrecorded vortex phase distributions are calculated by diffraction theory. By seriating these phase maps, the spiral phase structure and propagation of optical vortex can be displayed in real time.